Glans ischemia after circumcision and dorsal penile nerve block: Case report and review of the literature - Garrido-Abad, Pablo (Urol Ann, 2015)
Circumcision is an easy commonly performed surgical procedure in childhood. However, it is not free of a low number of complications, (1-5-5%). Here we report a case of a 3-year-old boy with glans superficial necrosis after circumcision, managed with topical (nitroglycerin, gentamicin), oral (pentoxifylline) and epidural (urgent caudal block with bupivacaine) treatment. A review of the literature and the different treatments reported by other authors was done. After 7 days of treatment, local signs of ischemia and severe pain disappeared, without adverse events related to treatment. Although the ischemia or necrosis of the glans after circumcision are rare, we may suspect them in case of presence of severe acute pain or dark color. We report the successful management of this complication.